2017
DOI: 10.1111/bcpt.12686
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Metabolic Profile of Inhaled Budesonide and Salbutamol in Asthmatic Children during Acute Exacerbation

Abstract: Inhaled budesonide and salbutamol represent the most important and frequently used drugs in asthmatic children during acute exacerbation. However, there is still no consensus about their resulting metabolic derangements; thus, this study was conducted to determine the distinct metabolic profiles of these two drugs. A total of 69 children with asthma during acute exacerbation were included, and their serum and urine were investigated using high-resolution nuclear magnetic resonance (NMR). A metabolomics analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
(53 reference statements)
2
32
0
Order By: Relevance
“…Moreover, to normalize the skewed distributions, log transformations were used for non‐linear conversions of the data. To eliminate the effect of inter‐subject variability and to identify endogenous metabolites that contributed significantly to the classification, linear combinations of X variables orthogonal to the Y vector were removed by orthogonal projections to latent structures (OPLS)‐discriminant analysis (DA) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, to normalize the skewed distributions, log transformations were used for non‐linear conversions of the data. To eliminate the effect of inter‐subject variability and to identify endogenous metabolites that contributed significantly to the classification, linear combinations of X variables orthogonal to the Y vector were removed by orthogonal projections to latent structures (OPLS)‐discriminant analysis (DA) …”
Section: Methodsmentioning
confidence: 99%
“…To eliminate the effect of inter-subject variability and to identify endogenous metabolites that contributed significantly to the classification, linear combinations of X variables orthogonal to the Y vector were removed by orthogonal projections to latent structures (OPLS)-discriminant analysis (DA). 24,25 Metabolic network analysis To identify the most relevant metabolic pathways in cancer cachexia, pathway analysis was used for pathway-enrichment analysis and pathway-topology analysis. The metabolites with variable importance in the projection (VIP) scores >1.0 in PLS or p1 ≥ ± 0.05 in S-Plot were examined and selected for discrimination power according to multiple statistical criteria.…”
Section: Metabolomics Analysismentioning
confidence: 99%
“…Taurine and taurine metabolism were also found to increase after asthma treatment (Comhair et al, 2015;Quan-Jun et al, 2017), which may be related to taurine inhibiting the production of inflammatory cytokines, reducing nasal friction and histamine (Nam et al, 2017). TCA cycle (Quan-Jun et al, 2017;Khoo et al, 2018;Chen et al, 2019) and phenylalanine, tyrosine, and tryptophan biosynthesis (Zinkeviciene et al, 2016) has also been found to be of some significance in the study of metabolomics of many allergies. These findings have certain indications and auxiliary effects for researchers to further discover the mechanism of SCIT for allergic rhinitis.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, decreased levels of prolylhydroxyproline (ProHyp) and pipecolic acid were found in urine and were associated to an increased risk of osteoporosis and bone injury due to CS treatment (31). Metabolomics was also used to evaluate the effect of a combined treatment of budesonide and salbutamol in children during asthma acute exacerbation (36). Arginine and proline metabolism, as well TCA cycle, were the most impacted pathways.…”
Section: Research and Clinical Valuementioning
confidence: 99%